The timing of fluid intake during an Olympic distance triathlon - McMurray, R. G.; Williams, D. K.; Battaglini, C. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
Seven highly trained male triathletes, aged 18 to 35 years, were tested during two simulated Olympic distance triathlons to determine whether run performance was enhanced when consuming 177 ml of water at 8, 16, 24, and 32 kilometers (Early Trials) compared to consumption at 10, 20, 30, and 40 kilometers (Late Trials), during the cycling segment of the triathlon. Swim times for 1500 m were similar between trials; 40-km cycling times were ~10 s faster during the Late Trials; however, 10-km run times were faster during the Early Trials (P < 0.02). No significant differences between run trials were found for the rating of perceived exertion, oxygen uptake, heart rate, and change in urine specific gravity. It was concluded that the consumption of fluids earlier in the cycle phase of the Olympic distance triathlon benefits the run and overall performance time.